Rapid oxidative degradation of methylene blue by various metal oxides doped with vanadium. Issue 47 (27th May 2015) - Amini, Mojtaba; Ashrafi, Mahdi; Gautam, Sanjeev; Chae, Keun Hwa
<x xml:space="preserve">Abstract</x> The oxidative degradation of methylene blue in the presence of various metal oxides doped with vanadium was studied.